Pengaruh Suhu dan Waktu Pemanasan terhadap Nilai HGI pada Sampel Batubara di PT. Bukit Asam Tbk - Ghony, Muhammad Abdul (ARKA INSTITUTE, 2022)
HGI is a laboratory measurement of the ease or difficulty of grinding or pulverizing coal. The grinding index value determines the time and effort required to grind coal to a certain fineness. This test is determined by preparing a certain grain size to be ground using a machine under standard conditions and the amount of coal being crushed is compared to the standard linearity of coal. The HGI standard values ​​that have been certified using ASTM standards are 32, 49, 65, and 95. This study consisted of variables, namely temperature and heating time, and related variables, namely HGI values. HGI data retrieval after heating minutes was carried out on coal samples with heating temperatures of 50˚C, 100˚C, 150˚C and 200˚C and heating times of 30 minutes, 60, 90 minutes and 120 minutes. The condition of the optimum HGI value was obtained at a heating temperature of 100℃ and a time of 60 minutes with an HGI value of 70.2558,. This index is very helpful in assessing the capacity of the mill used to grind coal to the required size for feed to the furnace besides HGI also affects how the coal is distributed in the lifting equipment properly.